BIOAKTIVITAS REPELAN EKSTRAK DAUN TEMBELEKAN (Lantana camara) TERHADAP NYAMUK CULEX - Sutrisnawati Mardin (Postgraduate, University of Mataram, 2025)
The increasing resistance of mosquitoes to chemical insecticides, which negatively impacts the environment, necessitates alternative plant extract usage to mitigate these effects. The objective of this study was to evaluate the bioactivity of Lantana camara leaf extract as a repellent against Culex mosquitoes. L. camara leaves were extracted using the maceration method. Concentrations of 1%, 2%, 3%, and 4% L. camara leaf extract were used to test repellent efficacy. The arm-in-cage method was used to assess effectiveness. Key parameters observed included the number of mosquito landings, time to first bite, and duration of protection. Results indicated that a 4% concentration of L. camara leaf extract provided optimal protection, reducing mosquito landings by up to 90% and offering a two-hour protection duration. This efficacy was comparable to commercial repellents, which provided 96% protection. These findings suggest that L. camara leaf extract has the potential to serve as an effective, safe, and environmentally friendly mosquito repellent.